Identification and Antifungal Susceptibility Profiles of Candida nivariensis and Candida bracarensis in a Multi-Center Chinese Collection of Yeasts - Hou, Xin; Xiao, Meng; Chen, Sharon C.-A.; Wang, He; Yu, Shu-Ying; Fan, Xin; Kong, Fanrong; Xu, Ying-Chun (Frontiers in Microbiology, 2017)
Candida nivariensis and Candida bracarensis are two emerging cryptic species within the Candida glabrata complex. Thirteen of these isolates from 10 hospitals in China were studied for their species identification and antifungal susceptibilities. Phenotypic and molecular (rDNA ITS sequencing, D1/D2 sequencing and ITS sequencer-based capillary gel electrophoresis [SCGE]) and MALDI-TOF MS identification methods were compared for their performance in species identification. Twelve of 13 (92.3%) isolates were identified as C. nivariensis and one as C. bracarensis using ITS sequencing as the reference method. Results obtained by D1/D2 sequencing and ITS SCGE were concordant with ITS sequencing results for all (100%) isolates. SCGE was able to subtype 12 C. nivariensis into four ITS SCGE length types (LTs). All isolates failed to be identified by the Vitek MALDI-TOF MS system (bioMérieux), whilst the Bruker MS system (Bruker Daltoniks) correctly identified all C. nivariensis isolates but using a lowered (≥1.700) cut-off score for species assignment; the C. bracarensis isolate was identified but with score <1.700. The Vitek 2 Compact system could not identify 11 C. nivariensis and one C. bracarensis isolate and misidentified the remaining C. nivarensis strain as “C. glabrata”. All isolates were susceptible-dose dependent (S-DD) to fluconazole (MIC range 0.5-4μg/mL) and were classed as susceptible to echinocandins (MICs ≤0.06μg/mL). All 13 isolates had low MICs for other azoles (MICs ≤0.5μg/mL), amphotericin B (MICs ≤2μg/mL) and 5-flucytosine (MICs ≤ 0.25μg/mL). Our results reinforce the need for molecular differentiation of species of C. nivarensis and C. bracarensis. The performance of MALDI-TOF may be improved by adding mass spectral profiles (MSPs) into the current databases. The antifungal susceptibility profile of isolates should be monitored.